IGF2BP1 promotes proliferation of neuroendocrine neoplasms by post-transcriptional enhancement of EZH2 - Sperling, Florian; Misiak, Danny; Hüttelmaier, Stefan; Michl, Patrick; Griesmann, Heidi (Cancers, 2022)
EZH2; H3K27me3; IGF2BP1; NEN; RNA-binding protein; cell cycle